Editorial Vol4 no1 - Irene Stevens (Scottish Journal of Residential Child Care)
One of the key skills in residential child care practice is assessment. In this edition of the journal, several writers have taken some aspect of assessment as their theme, be it risk assessment, assessment of new staff, or a tool for assessing the needs of care leavers.